Using Estrus-Detection Patches to Vary Time of Insemination Improves Pregnancy Rates Compared with One Single Timed Insemination - S. L. Hill; D. M. Grieger; K C Olson; J. R. Jaeger; J. S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 2016)
Timed artificial insemination (TAI) of beef cows at a predetermined time is a management tool that reduces labor costs associated with conventional heat detection before insemination. Multiple research trials have examined timing of the individual components of the developed protocols associated with TAI. The 7-day CO-Synch + progesterone insert (controlled internal drug release; CIDR) protocol has been shown to initiate ovulation effectively in cycling and noncycling suckled beef cows, often producing pregnancy rates greater than 50% in beef cows. In the current research, we examined using two targeted insemination intervals depending on the occurrence of estrus. We hypothesized that by more closely synchronizing estrus and insemination that pregnancy rates would be increased. We further hypothesized that cows that do not demonstrate estrus and are subjected to a TAI protocol might benefit from an increased interval to insemination.
Keywords: Beef Cattle Research